Planning And Evaluation of Technological System Development in Public Street Lighting to Support Sustainable Development of The Integrated City of Batam - Morwanto, Gatot; Sidabutar, Yuanita FD; Suciati, Herlina; Panusunan, Panusunan (Graduate Program Magister Manajemen Pendidikan, 2023)
Developing a smart public street lighting system involves the integration of advanced technologies to improve energy efficiency, reduce operational costs, enhance safety, and enable intelligent functionalities. This research discusses the planning and evaluation of the development of a smart public street lighting system in the Batam City area with the aim of increasing the sustainability of the smart city. The research method used is a case study to gain an in-depth understanding of existing lighting systems and involve relevant stakeholders, such as local governments, technical experts and local communities. The evaluation results show that the development of a smart public street lighting system has a positive impact on the sustainability of smart cities, increasing energy efficiency, safety and community participation. The integration of local wisdom and maritime aspects in planning intelligent public street lighting systems also makes an important contribution to the identity and sustainability of Batam City. This research recommendations for further development, strengthening local wisdom, collaboration and partnerships with the private sector, as well as expanding implementation to other regions.